(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The forensically-important Dipteran flies, Lucilia sericata and Megaselia scalaris, complete their life-cycles in perishable, filthy, unhygienic and fowl-smelled natural diets, which hinder the rearing work and the indoor environment of laboratory. To overcome this unhygienic condition, a newly formulated simple, comparatively more hygienic one was prepared and evaluated for the rearing of these two flies. This artificial diet, when compared to their natural diets for rearing at different temperatures, it demonstrated no significant difference for their developmental durations. Statistical analyses proved that the difference between the natural and formulated diet was not responsible for their developmental durations; rather their rearing temperatures played a significant role in this respect. Taken together, these findings showed that the newly formulated artificial diet might facilitate the hygienic and easy rearing of these flies for forensic and medical entomology as well as other research purposes in terms of nutrition, cost-effectiveness and availability of the ingredients of diets. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (2), 86-92